ROLE OF ARCHITECTURE SPACES IN CONTROLLING INFECTIOUS DISEASE: A CASE OF COVID-19 MANAGEMENT IN LAHORE, PAKISTAN - Mamuna Iqbal; Tayyab Javaid; Usman Awan (International Journal of Contemporary Issues in Social Sciences, 2024)
Covid 19 had a great impact on the lives of people all over the world, while it had many serious implications, one of the most important ones was the quarantine and the isolation that came with it (Ferreira, et al., 2022). With this, the world came to learn the importance of the built environment and how its quality impacted not just the quality of life in the quarantine but also the management of the disease. This research examines the impact of architectural spaces on the management of COVID-19, it is done through a comparative analysis of the Expo Center Lahore and the Pakistan Kidney and Liver Institute (PKLI) as they both were converted into a COVID-19 quarantine center during the COVID-19 pandemic. This Research is based on qualitative data and analysis through two means, first is the analysis of architectural spaces done through observations and architectural drawings. Second is the interviews of patients who stayed in these quarantine centers and the interviews of staff who managed them. The analysis included functional aspects of design, disease control, artificially adopted healthcare, and social characteristics as external variables that predict patient satisfaction levels during quarantine. Results showed that the sense of privacy, mental health, isolation, and patient and staff safety regarding infectious diseases are the most important features defining the success of these centers. Research also indicated the need to review the infectious disease healthcare regulation on healthcare by-laws.